Modelado y prototipado de una férula para limitar el movimiento de las extremidades superiores en niños con capacidades especiales en la escuela Carlos Garbay Montesdeoca - Trujillo Zuñiga, Kevin Brandon (2023)
One of the most frequent consequences of a cerebral vascular accident is that can occur during the embryo development or birth, provoking disabilities to those affected by it. Cerebral vascular accident can affect the motor skills, resulting in atrophies due to the lack of movement of the muscle and tendons. In this project of investigation, we present the design and the prototype implementation of a dynamic splint; to control the flexion- extension angle of the superior extremities in children with special abilities, by using the technology of 3D impression, to help minimize the involuntary flexor movements that can present during the day. To validate the prototype of the dynamic splint system, trials were conducted with three children from the Carlos Garbay Montesdeoca School. The processed data obtain shows that 90% of the angles were centered above the minimum angle allowed. The same way it was tested minimizing movement with three different activities; refreshment, classes and an exam. As a result of this experiment it was observed that during refreshment activity the child maintains high values of flexion extension angle, this shows the child that the child while developing his activity maintains the extension for a long time. In the class activity, the child shows a different behavior since he maintains low flexion-extension angle values, very close to the minimum angle allowed and for a long time. In the test activity it is notice that the child’s behavior is not that different from the previous activity, however there are values of the flexion-extension angle higher than the minimum angle allowed. In conclusion, the splint allows free movement of the arm for its extension and limits flexion as required, this does no influence other movements of the arm such as supination and pronation of the forearm.